PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 188 PEKANBARU - Dina Asih Veronica; Syahrilfuddin Syahrilfuddin; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The study of this classroom action research is aimed to determine the improvement of student’s outcomes of learning mathematics after implementation the approach of Indonesian Realistic Mathematics Education (PMRI) in III grade students SDN 188 Pekanbaru. This research was conducted in two cycle. The Subject of the study were 38 students of class III, consisting of 23 male students and 14 female students. Tehcniques of collecting data about activities of the teacher and student on mathematics subjects using observation methods and data collection about outcomes of learning mathematics using test methods. The result of this research is showed increase in student’s outcomes of mathematics subject from cycle I to cycle II. The learning result before the action that reaches the Value of Completeness is only 10 students with the percentage mastery 27.02%. In the preliminary data the average mathematical result is 59.29. Then on the cycle I students who achieve the value of mastery increased as many as 10 students to 26 students with a percentage mastery 70.27%. In the cycle I of student learning outcomes increased by 12.19 points to 71.62. In the cycle II students who achieve the value of mastery increased by 7 students to 33 people with a percentage of completeness 89.19%. The average student's mathematics learning outcomes increased by 8.92 points to 80.40.Keywords: Indonesian Realistic Mathematics Education (PMRI), Learning Outcomes Mathematics